2022
DOI: 10.1038/s12276-022-00780-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical investigation of artesunate as a therapeutic agent for hepatocellular carcinoma via impairment of glucosylceramidase-mediated autophagic degradation

Abstract: Artesunate (ART) has been indicated as a candidate drug for hepatocellular carcinoma (HCC). Glucosylceramidase (GBA) is required for autophagic degradation. Whether ART regulates autophagic flux by targeting GBA in HCC remains to be defined. Herein, our data demonstrated that the dramatic overexpression of GBA was significantly associated with aggressive progression and short overall survival times in HCC. Subsequent experiments revealed an association between autophagic activity and GBA expression in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…It was reported that overexpression of GBA could accelerate the progression of hepatocellular carcinoma and affect its poor prognosis. 65 In our study, the level of Cer(d18:1/20:0) in the sphingolipid signaling pathway was reduced after DWYG pretreatment, which might be related to its inhibiting effect on GBA of DWYG. Collectively, our results not only confirmed that these 7 key targets had an essential effect on the protection of ALI by DWYG, but also verified that the results of integrated metabolomics and network pharmacology analysis were credible.…”
Section: Discussionsupporting
confidence: 50%
“…It was reported that overexpression of GBA could accelerate the progression of hepatocellular carcinoma and affect its poor prognosis. 65 In our study, the level of Cer(d18:1/20:0) in the sphingolipid signaling pathway was reduced after DWYG pretreatment, which might be related to its inhibiting effect on GBA of DWYG. Collectively, our results not only confirmed that these 7 key targets had an essential effect on the protection of ALI by DWYG, but also verified that the results of integrated metabolomics and network pharmacology analysis were credible.…”
Section: Discussionsupporting
confidence: 50%
“…Concurrently, the ATS moiety triggered both the apoptosis and autophagy cell death processes. It inhibited the degradation of autophagosomes in cancer cells, thus leading to the autophagosome accumulation, which in turn aggravated cell death. , Moreover, ATS was identified to be a specific activator of ferroptosis in cancer cells , and exerted antitumor activity via remodeling the immunosuppressive microenvironment . Therefore, 10f displayed both potent in vitro and in vivo antitumor activities via targeting multiple targets and pathways, and all of these interactions jointly led to the death of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that 10f elevated the protein expression of SQSTM1/p62 in a concentration-dependent manner. Recently, Zhang’s group reported that ATS directly inhibited glucosylceramidase activity and then the degradation of autophagosomes in cancer cells was inhibited, thus leading to the autophagosome accumulation that was responsible for the antitumor effect of ATS . Therefore, the ATS moiety of 10f was responsible for the accumulation of autophagosomes, which was favorable for the antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…DGE (Differential gene expression) analysis was performed on the whole dataset, and 36 PC genes were identified to be differentially expressed from ML identified genes (Figure 3(F)) . After that using lasso penalized coz regression analysis theses 55 PC genes were reduced to 13 genes SEMA3F [51], B4GALNT1 [7], COLEC10 [52], CEP131 [53], APLN [54], GBA [55], SCAMP3 [56], TOMM40L [57], PYGO2 [58] and PLVAP [59] has been reported in literature while CAPN11, SPTY2D1OS and C14orf180 is not so far has been studied in LIHC. Additionally, these 13 genes from survival analysis predicted to be prognostic genes for OS of LIHC cases.…”
Section: Discussionmentioning
confidence: 99%